2005
DOI: 10.2174/1381612054546833
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Local Anesthetic Drug Action on Voltage-Gated Sodium Channels

Abstract: Local anesthetic drugs interfere with excitation and conduction by action potentials in the nervous system and in the heart by blockade of the voltage-gated Na channel. Drug affinity varies with gating state of the channel. The drugs show low affinity at slow excitation rates, but high affinity when the channels are opened and inactivated during action potentials at high frequency, as they are during pain or during a cardiac arrhythmia. The drugs are thought to access their binding site in the inner pore by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 73 publications
5
92
0
1
Order By: Relevance
“…Fenestration size is modulated by S6 bending, which we have proposed may be associated with a collapse into an inactivated state. These observations suggest that the binding of drugs at this crucial site could modulate conversion to a slowinactivated state, as suggested experimentally (28,31,32,46). These simulations have therefore proven to be important for exploring the roles of protein flexibility in ion conduction mechanisms and have given us clues as to the molecular-level processes that underscore inactivation and drug inhibition of Na v channels.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Fenestration size is modulated by S6 bending, which we have proposed may be associated with a collapse into an inactivated state. These observations suggest that the binding of drugs at this crucial site could modulate conversion to a slowinactivated state, as suggested experimentally (28,31,32,46). These simulations have therefore proven to be important for exploring the roles of protein flexibility in ion conduction mechanisms and have given us clues as to the molecular-level processes that underscore inactivation and drug inhibition of Na v channels.…”
Section: Resultsmentioning
confidence: 64%
“…It has been suggested that drugs can enter the cavity (48) and physically block the channel (49), or bind at the level of the opening via π-π stacking of aromatics (47) and inhibit the current by favoring a nonconductive inactivated state (46). Moreover, it is known that slow inactivation is affected by local anesthetics or antiepileptics drugs (30)(31)(32) and by the mutation of the same Phe involved in drug binding (28). Evidence suggests that drug binding affinity varies depending on the conducting state of the channels (46), corroborating our own observations that accessibility of both the Phe and cavity openings are codependent and correlated with changes in the S6 helix and gate collapse, suggesting a transition to the inactivated state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Second, both LAs and DCJW are believed to bind preferably to slow-inactivated channels (10,16,25). In the case of LAs, the preference is likely due to the lack of electrostatic repulsion between the ligand charged group and the cationdeficient outer pore (13).…”
Section: Resultsmentioning
confidence: 99%
“…SCBIs are believed to bind to and trap sodium channels in non-conducting slow inactivated states (9), the mechanism similar to that proposed for local anesthetics (LAs) (1,10). Molecular interactions of LAs with mammalian sodium channels have been intensively studied (11,12).…”
mentioning
confidence: 98%